Low coherence fiber optic system for remote sensors illuminated by a 1.3 μm multimode laser diode - Lobo Ribeiro, Antonio B. (1993)
A fiber optic sensor probe, with two low‐finesse Fabry–Perot cavities enabling the determination of displacement (in the range of a typical diaphragm pressure sensor) and temperature, is described. The sensors are connected in a reflective array network and their status is read using coherence tuned sensing based upon a multimode laser diode at 1.3 μm wavelength. Data are presented which show the resolution and linearity of the sensors for the measurement of displacement and temperature.